CAR-T cell therapy in older adults with relapsed/refractory LBCL: benefits and challenges - Matthew J Frigault; Peter A Riedell; Leyla Shune (Journal for ImmunoTherapy of Cancer)
Patients with relapsed or refractory diffuse large B-cell lymphoma (r/r DLBCL) have poor prognosis with a high unmet need for efficacious treatment options. Most patients with r/r large B-cell lymphoma (LBCL) are elderly, which adds to the complexity of choosing the appropriate and effective therapy in these patients. Recently approved therapies, such as CD19-targeted chimeric antigen receptor-T cell therapy, have shown improvements in the outcomes of patients with r/r DLBCL. Several real-world studies also support the use of these newer therapies in elderly patients. However, given the frailty, variability in the risk factors in each elderly patient, and the increased susceptibility for adverse events, a comprehensive geriatric assessment and a multidisciplinary approach could be helpful in guiding the management and treatment choices for these vulnerable patients. Individualized care can aid in giving elderly patients with r/r LBCL the best possible outcome with their chosen treatment regimen.